Logistics Basics -- Exercises -- Case Studies - Gleissner, Harald; Femerling, J. Christian (Springer Texts in Business and Economics, 2013)
Logistics is the ideal book for Bachelor students of logistics, providing a solid foundation as well as a practical guide. In modular and clear form, it explains key concepts, principles, and practices of logistics. Learning objectives as well as several case studies are integrated into each chapter. It features chapters on Principles of Logistics; Logistics Systems; Transport Systems and Logistics Services; Warehousing, Handling and Picking Systems; Inventory, Stock and Provisioning Management; Logistics Network Planning; IT in Logistics; and Logistics Controlling. In addition, the second fully updated German edition has been extended by the chapters Logistics Infrastructure and Investment and Financing in Logistics